Consumer Religiosity and Its Influence on Their Uptake and Consumption of Edible Insects among Selected Communities in Western Kenya - Ogal, Pascal Otieno; Ayieko, Monica; Angira, Charles (African Journal of Climate Change and Resource Sustainability, 2022)
Global food demand is expected to rise due to the population increase estimated to reach 9.5 billion by the year 2050. As a result, the available natural resources such as water sources and land will become scarce and overused. Indisputably, other sustainable food resources need to be identified and practised to solve the problem of food inadequacy. The world population will be encouraged to eat less consumed food resources. Edible insects have been identified as sustainable food resource that is rich in protein and other nutrients. Even though it is still facing rejection among certain consumers due to unknown reasons, factors influencing entomophagy have now been studied from different angles of the world communities. A descriptive research design with both qualitative and quantitative methodology was employed, using a semi-structured questionnaire loaded in an Open Data Kit (ODK) Collect software. Additionally, a simple random sampling technique was used to measure the following constructs. Demographics, religiosity on the consumption of insects, contrasting beliefs among the selected religious societies on edible insects’ consumption. There was an association between religious restriction and the consumption of edible insects at a P-value less than 0.05. However, it is unclear why individuals from religious groupings would choose not to consume insects while others condone the practice. The eating of insects is cited in religious doctrines. Nonetheless, there is still low consumption of edible insects among different religious believers. Religiosity has deterred individuals from indulging in certain food items. How comes they do not indulge in what their doctrines recommend? We, therefore, wish to find out why religion has not encouraged persons to adopt entomophagy. This study, therefore, seeks to examine the influence of religiosity on the consumption and uptake of edible insects among the selected communities in Western Kenya. The data for this study will be collected through the administration of a well-formulated electronic questionnaire and multivariate qualitative models.
Keywords: Entomophagy; Religiosity; Edible-Insects; Consumptions; Doctrines